Effect of body mass index on the outcomes of controlled ovarian hyperstimulation in Chinese women with polycystic ovary syndrome: a multicenter, prospective, observational study - Sheng, Yan (J Assist Reprod Genet, 2016)
PURPOSE: The purpose of the present study is to explore the influence of body mass index (BMI) on outcomes of in vitro fertilization/intracytoplasmic sperm injection (IVF/ICSI) techniques in Chinese women with polycystic ovary syndrome (PCOS). METHODS: This was a multicenter, prospective, observational study that enrolled 800 subjects with PCOS from nine hospitals in China. Patients were categorized according to BMI categories: underweight, <18.5 kg/m(2); normal, 19–23.9 kg/m(2); overweight, 24–27.9 kg/m(2); and obese, ≥28 kg/m(2). Total recombinant follicle-stimulating hormone (rFSH) dose used, estradiol, and progesterone levels on human chorionic gonadotropin (hCG) day; implantation rate; and biochemical, clinical, and ongoing pregnancy rates were compared among BMI categories. Hormone levels (estradiol, follicle-stimulating hormone (FSH), LH, testosterone, and progesterone) were measured using electrochemiluminescence assays. RESULTS: Among the 774 subjects, 27.3 % were overweight and 8.1 % were obese. The rFSH dose used differed significantly among BMI categories (P < 0.001). The implantation rate was lower in obese subjects than that in normal-weight subjects (25.3 vs 45.7 %). Clinical pregnancy rate per transfer differed among BMI categories (P = 0.033), but there was no difference for biochemical (P = 0.327) and ongoing (P = 0.084) pregnancy rates. The miscarriage rate was similar among BMI categories. CONCLUSIONS: More than one third of Chinese women with PCOS undergoing IVF/ICSI are overweight or obese. Elevated BMI is associated with reduced clinical pregnancy rate but similar ongoing pregnancy rates, suggesting that BMI has little impact on IVF outcomes. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s10815-016-0830-1) contains supplementary material, which is available to authorized users.